Dabrowski's Overexitabilities, the Big Five, Intelligence, and GPA. - Dorn, Stephanie L. (My University, 2009)
According to Dabrowski, some individuals display Overexcitabilities, or intensities, in up to five dimensions: Intellectual, Imaginational, Emotional, Psychomotor, and Sensual (Mendaglio & Tillier, 2006). Reviews of the literature reveals both a relationship between high intelligence and specific Overexcitabilities--Intellectual, Imaginational, Emotional (Mendaglio & Tillier) and a relationship between intelligence and specific Big Five factors--Conscientiousness and Openness to Experience but not to Neuroticism, Extraversion, Agreeableness (Asendorpf & Van Aken, 2003). We conducted a study to test these assertions.
Color poster with text and charts (Spring 2009)
Keywords: Intellect--Psychological aspects; Gifted persons--Psychology; Posters